Respuesta :
Answer:
x = 12 and y = -9
Explanation:
Given:
2 x +3y = -3
3x + 5y = -9
make x the subject:
[tex]2 x +3y = -3[/tex]
[tex]2x = -3 - 3y[/tex]
[tex]x = \frac{-3 - 3y}{2}[/tex] _____equation 1
[tex]3x + 5y = -9[/tex]
[tex]3x = -9-5y[/tex]
[tex]x = \frac{-9-5y}{3}[/tex] ______equation 2
solve them simultaneously:
[tex]\frac{-9-5y}{3} = \frac{-3 - 3y}{2}[/tex]
[tex]2(-9-5y) = 3(-3-3y)[/tex]
[tex]-18-10y = -9 - 9y[/tex]
[tex]-10y + 9y = -9 + 18[/tex]
[tex]-y = 9[/tex]
[tex]y = -9[/tex]
now solve for x:
[tex]2 x +3y = -3[/tex]
[tex]2x + 3(-9) = -3[/tex]
[tex]2x -27 = -3[/tex]
[tex]2x = -3 + 27[/tex]
[tex]2x = 24[/tex]
[tex]x = 12[/tex]
coordinates where they both intersect is (12,-9) at one point so they have one solution
Answer:
x = 12
y = -9
The system has one solution as it has one point of intersection at (12, -9)
Step-by-step explanation:
Equation 1: [tex]2x + 3y = -3[/tex]
Equation 2: [tex]3x + 5y = -9[/tex]
Rewrite equation 1 to make [tex]x[/tex] the subject:
[tex]2x + 3y = -3[/tex]
[tex]\implies 2x = -3 - 3y[/tex]
[tex]\implies x = -\dfrac32 - \dfrac32 y[/tex]
Substitute this into equation 2 and solve for [tex]y[/tex]:
[tex]3( -\dfrac32 - \dfrac32 y)+5y=-9[/tex]
[tex]\implies -\dfrac92 - \dfrac92 y+5y=-9[/tex]
[tex]\implies -\dfrac92 +\dfrac12 y=-9[/tex]
[tex]\implies \dfrac12 y=-\dfrac92[/tex]
[tex]\implies y=-9[/tex]
Substitute y = -9 into one of the equations to find [tex]x[/tex]:
[tex]2x + 3(-9) = -3[/tex]
[tex]\implies 2x - 27 = -3[/tex]
[tex]\implies 2x = 24[/tex]
[tex]\implies x=12[/tex]